Mediators of Inflammation in Polycystic Ovary Syndrome in Relation to Adiposity - Thozhukat Sathyapalan; Stephen L. Atkin (Hindawi Limited, 2010)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age group and is associated with a higher cardiovascular risk. Obesity, mainly visceral adiposity, is prevalent in patients with PCOS. Obesity is associated with low-grade inflammation and raised inflammatory cytokines, both of which are also described in patients with PCOS. In this paper, the potential relationships between fat distribution, adipocyte dysfunction and, altered inflammatory markers in patients with PCOS have been discussed.